Characteristics and Management Implications of the Spring Waterfowl Hunt in the Western Canadian Arctic, Northwest Territories - Bromley, Robert G. (ARCTIC, 1996)
The species composition, timing of the harvest, sex, age, breeding status, and numbers of geese and swans shot during the spring hunt by residents of Tuktoyaktuk, Paulatuk, and Sachs Harbour, Northwest Territories were studied in each community hunting area for three consecutive years (1987 to 1990). Investigators visited hunters repeatedly in the field, conducting interviews and examining >=27% of the reported harvest. Snow geese (Anser caerulescens caerulescens) accounted for 70% of the harvest, followed by white-fronted geese (Anser albifrons frontalis, 19%), Canada geese (Branta canadensis hutchinsii, 5%), brant (Branta bernicla nigricans, 4%), tundra swans (Cygnus columbianus, 2%), and Ross' geese (Anser rossii, <1%). Sex ratios varied by species and community. Age ratios (yearlings per adult) also varied, and were inversely correlated with the size of the previous year's continental recreational harvest for white-fronted geese. Breeding status of geese with adult plumage varied, but was generally near 80% breeders. Average annual harvest of geese and swans were estimated at 5986 for Tuktoyaktuk, 1605 for Paulatuk, and 2790 for Sachs Harbour. Regional spring harvests, as a percent of continental harvests of regional populations, were 19% for lesser snow geese and 15% for white-fronted geese. Harvest levels require consideration in all stages of management of the resource, from local to continental. Action is required in Canada, through cooperative wildlife management mechanisms of the Inuvialuit Final Agreement and other land claims legislation, and through new regional bodies, to ensure that the spring harvest is incorporated into regional, national and international management of migratory birds. Durant trois années consécutives (de 1987 à 1990), on a étudié la composition des espèces, le moment des prélèvements, le sexe, l'âge, le statut de reproducteur et le nombre d'oies et de cygnes tués par balle au cours de la chasse printanière par les résidents de Tuktoyaktuk, de Paulatuk et de Sachs ...